Emergence of a novel drug resistant H7N9 influenza virus: evidence based clinical potential of a natural IFN-α for infection control and treatment - Liu, Qinfang; Ma, Jingjiao; Strayer, David R.; Mitchell, William M.; Carter, William A.; Ma, Wenjun; Richt, Juergen A. (My University, 2013)
The novel avian H7N9 influenza virus has caused more than 130 human infections with 43 deaths in China. Because of the lack of existing immunity against H7 subtype influenza viruses in the human population and the absence of a licensed commercial vaccine, antiviral drugs are critical tools for the treatment of infection with this novel H7N9. Both M2-ion channel blockers and neuraminidase inhibitors are used as antiviral drugs for influenza infections of humans. The emerging H7N9 viruses are resistant to the M2-ion channel blockers because of a S31N mutation in the M2 protein; additionally, some H7N9 isolates have gained neuraminidase R292K substitution resulting in broad resistance to neuraminidase inhibitors. In this study we report that Alferon N can inhibit wild type and 292K H7N9 viruses replication in vitro. Since Alferon N is approved for clinical use, this would allow a rapid regulatory approval process for this drug under pandemic threat.
Keywords: H7N9; Alferon N; Neuraminidase inhibitors; Antiviral drug; Influenza; Tamiflu; Oseltamivir resistance